Primary Commodity Prices : Co-movements, Common Factors and Fundamentals - Byrne, Joseph P.; Fazio, Giorgio; Fiess, Norbert (2012)
The behavior of commodities is critical for developing and developed countries alike. This paper contributes to the empirical evidence on the co-movement and determinants of commodity prices. Using nonstationary panel methods, the authors document a statistically significant degree of co-movement due to a common factor. Within a Factor Augmented VAR approach, real interest rate and uncertainty, as postulated by a simple asset pricing model, are both found to be negatively related to this common factor. This evidence is robust to the inclusion of demand and supply shocks, which both positively impact on co-movement of commodity prices.